Effect of terbutaline on hyperpnoea-induced bronchoconstriction and urinary club cell protein 16 in athletes - Simpson, A. J.; Simpson, A. J.; Tufvesson, E.; Tufvesson, E.; Anderson, S. D.; Anderson, S. D.; Romer, L. M.; Romer, L. M.; Bjermer, L.; Bjermer, L.; Kippelen, P.; Kippelen, P. (Journal of Applied Physiology, 2013)
Repeated injury of the airway epithelium caused by hyperpnoea of poorly conditioned air has been proposed as a key factor in the pathogenesis of exercise-induced bronchoconstriction (EIB) in athletes. In animals, the short-acting β2-agonist terbutaline has been shown to reduce dry airflow-induced bronchoconstriction and the associated shedding of airway epithelial cells. Our aim was to test the efficacy of inhaled terbutaline in attenuating hyperpnoea-induced bronchoconstriction and airway epithelial injury in athletes. Twenty-seven athletes with EIB participated in a randomized, double-blind, placebo-controlled, crossover study. Athletes completed an 8-min eucapnic voluntary hyperpnoea (EVH) test with dry air on two separate days 15 min after inhaling 0.5 mg terbutaline or a matching placebo. Forced expiratory volume in 1 s (FEV1) and urinary concentration of the club cell (Clara cell) protein 16 (CC16, a marker of airway epithelial perturbation) were measured before and up to 60 min after EVH. The maximum fall in FEV1 of 17 ± 8% (SD) on placebo was reduced to 8 ± 5% following terbutaline (P < 0.001). Terbutaline gave bronchoprotection (i.e., post-EVH FEV1 fall
Keywords: Physiology (medical); Physiology; exercise-induced bronchoconstriction; epithelial injury; Clara cell